Socio-Legal Analysis of the Detention of Children Under Police Investigation in the Bone Police Jurisdiction - Mukhawas Rasyid; Suriyati Suriyati; Muh. Bakri; Gustika Sandra (Journal of Public Representative and Society Provision, 2026)
The problem of child crime is a very complex problem in its handling which is increasing every year. Indonesia as a country that ratified the Convention on the Rights of the Child which regulates the principle of legal protection for children has an obligation to provide special protection for children in conflict with the law. The purpose of this study is to examine the detention of children as perpetrators of criminal acts at the investigation level in the jurisdiction of the Bone Police in accordance with the provisions of Law Number 11 of 2012 concerning Juvenile Justice. This research method uses an empirical juridical approach, namely a legal approach that combines normative aspects (Law as regulations) with empirical aspects not only looking at written legal rules, but also how these rules are applied and understood in the practice of community life. The research results showed that the implementation of detention of child suspects at the Bone Police Department has been optimal, as stipulated in Law Number 11 of 2012 concerning Juvenile Justice, specifically regarding child detention. Obstacles identified include the absence of a dedicated unit to handle child issues, a lack of professional staff, limited budgets for the investigation process, and the lack of government involvement in implementing policies on juvenile justice. It is recommended that the local government and the police collaborate to disseminate information on laws and regulations regarding the child investigation process and legal protection for children in conflict.